Module categories over equivariantized tensor categories - Mombelli, Juan Martín (2017)
For a finite tensor category C and a Hopf monad T : C --> C satisfying certain conditions we describe exact indecomposable left C^T-module categories in terms of left C-module categories and some extra data. We also give a 2-categorical interpretation of the process of equivariantization of module categories.